2019
DOI: 10.5296/jsel.v7i1.14870
|View full text |Cite
|
Sign up to set email alerts
|

EFL Engineering Students’ Research Article Genre Knowledge Development through Concept Mapping Tasks: A Qualitative Interview-based Study

Abstract: This qualitative study explores how the use of concept mapping can function as a genre knowledge scaffold within an experimental course that aimed to teach EFL undergraduate students how to read primary research articles in their discipline. Using semi-structured student interviews, the study explored the development of the rhetorical, formal, process and content research article genre facets of three second-year Electrical and Computer Engineering students after working collaboratively on three specially desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This "peculiarity" in terms of structure often causes difficulties to novice readers and writers in CE departments who struggle both to read and write RAs (Seiradakis & Spantidakis 2018a). A solution to this problem could be designing and implementing EAP courses for CE students taking under consideration corpus-based research from relevant sub-disciplines and incorporating genre analysis tasks that emphasize specific rhetorical structures and linguistic forms derived from corpus analysis (Chang & Kuo 2011;Seiradakis & Spantidakis 2018b;Seiradakis & Spantidakis 2019). EAP genre-based courses employing a one-fits-all approach in academic writing usually end up providing theoretical declarative knowledge regarding genres which usually fails to become procedural outside classroom walls (Lee & Swales 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This "peculiarity" in terms of structure often causes difficulties to novice readers and writers in CE departments who struggle both to read and write RAs (Seiradakis & Spantidakis 2018a). A solution to this problem could be designing and implementing EAP courses for CE students taking under consideration corpus-based research from relevant sub-disciplines and incorporating genre analysis tasks that emphasize specific rhetorical structures and linguistic forms derived from corpus analysis (Chang & Kuo 2011;Seiradakis & Spantidakis 2018b;Seiradakis & Spantidakis 2019). EAP genre-based courses employing a one-fits-all approach in academic writing usually end up providing theoretical declarative knowledge regarding genres which usually fails to become procedural outside classroom walls (Lee & Swales 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A table depicting the types of studies we observed within the manuscript data are included in Table 1 and described further in the text below. Small numbers studies Smaller amount of data collected, Deeper understanding of phenomenon achieved in some cases [7], [40][41][42][43][44][45][46][47][48][49] Large numbers studies Articles within this category tended to have larger data sets with impressive efforts described to collect and conduct analysis on this data. The relationships that many authors had with the data could be described as being removed or separated and are described with examples in the following paragraphs.…”
Section: Resultsmentioning
confidence: 99%
“…Articles in this category tended to have fewer participants and, typically, less data. These articles ranged from a study with three participants [48] to one with 17 participants [7]. The amount of data also varied, with one study including one focus group [40] and another with one participant that had a large data set that was collected over four years and consisted of interviews, observations, field notes, artifacts, field notes, and focus groups [42].…”
Section: Small Numbers Studiesmentioning
confidence: 99%
See 1 more Smart Citation